Effect of thickness ratio of overlaying layer to hydrate bearing stratum upon the settlement of seabed sediments during Natural Gas Hydrate Dissociation. Issue 1 (June 2020) - Li, Hongbo; Ma, Shuzhi
Abstract: The dissociation of natural gas hydrate in the process of exploitation will weaken the mechanical properties of the surrounding soil, which will lead to the deformation and destruction of the seabed sediment, thus posing a potential threat to the safety of the undersea engineering infrastructures. In this paper, the finite difference method is used to simulate the vertical deformation of seabed sediments, and examine the effect of thickness ratio of the overlying layer to the HBS upon soil settlement via an established three-dimensional model of submarine hydrate mining. The main research results are as follows: The maximum settlement occurred at the top surface of HBS dissociation centre and the settlement decreased significantly from the mining well to the surrounding and from HBS to the overlying layer. The range of settlement trough on the top of HBS is far less than the overlaying layers. The thickness ratio of the overlying layer to the HBS will have a great influence on the distribution of sedimentation and deformation of seafloor sediments caused by hydrate dissociation. The deformation and the range of the settlement trough both decrease with the increasing thickness ratio of overlying layer to HBS. The research results will provide a strong theoretical reference for the stability of seabed and mining platform during hydrate mining.